The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.11648/j.ijass.20200802.11
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Impact of Weather Parameters on Signal Strength of Satellite Dish in Enugu Metropolis

Abstract: This research evaluates the impact of weather parameter (temperature, pressure, humidity and wind speed) on satellite dishes and how it affects the quality of reception it gives using the data obtained from the Automated Weather Station and Signal Strength in Enugu State University of Science and Technology. The atmospheric components and signal strength were measured every two minutes daily in different months, on different days, and at a different time of the day from the station for period of nine months. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…The increase in humidity in these months compared to March also contributed to the decrease in temperature, and by implication, increase in the signal strength. This result conforms with the works of [ 11 , 14 , 15 , 13 ,&6]] in which the signal strength recorded was found to be inversely proportional to temperature, wind speed, and atmospheric pressure, and directly proportional with relative humidity in their separate research works done in Benin city-Edo State, Enugu State, and Jos, Plateau State respectively.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The increase in humidity in these months compared to March also contributed to the decrease in temperature, and by implication, increase in the signal strength. This result conforms with the works of [ 11 , 14 , 15 , 13 ,&6]] in which the signal strength recorded was found to be inversely proportional to temperature, wind speed, and atmospheric pressure, and directly proportional with relative humidity in their separate research works done in Benin city-Edo State, Enugu State, and Jos, Plateau State respectively.…”
Section: Resultssupporting
confidence: 91%
“…Though some related works have been done such as the works by Refs. [ [12] , [13] , [14] ] in Benin city [ 15 ], in Enugu state [ 5 ] in Abuja and Jos, no work has been done on this radio station, Maloney FM Radio, Keffi since it was established in 2016, hence, making this research work very necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The attenuation caused by rainfall depends on various factors, such as the intensity of the rain, the size and shape of raindrops, and the distance between the transmitting and receiving antennas [4,5]. The effect of heavy or intense rainfall is more pronounced in tropical and subtropical regions where the frequency and intensity of rain occurrences are higher [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the size distribution of raindrops can vary depending on the geographical location, which in turn strongly influences the specific attenuation caused by rainfall and, consequently, the overall rain attenuation [8,9]. Rainfall intensity, on the other hand, can also vary significantly depending on the location and meteorological conditions, further impacting the extent of signal degradation caused by rainfall [7,10]. Furthermore, rainfall can also affect the polarization of the electromagnetic wave as it propagates through raindrops [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation